Mastectomy, HER2 Receptor Positivity, NPI, Late Stage and Luminal B-Type Tumor as Poor Prognostic Factors in Geriatric Patients with Breast Cancer - Demet Nak; Mehmet Kivrak (Diagnostics)
Background/Objectives: This study aims to explore the risk factors associated with poor survival outcomes in geriatric female patients with breast cancer. Methods: This study utilized data from the METABRIC database to evaluate the risk factors associated with poor survival outcomes among geriatric breast cancer patients. A total of 2909 female patients, 766 of whom were geriatric, were included in the study. The effects of the type of surgery; breast cancer types; cellularity; Estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) status; molecular class; axillary lymph nodes; Nottingham prognostic index (NPI); status of receiving systemic chemotherapy (SCT), hormone therapy (HT), and radiotherapy (RT); tumor size and tumor on overall survival (OS); and progression-free status (PFS) of geriatric patients were investigated. Additionally, the disease-specific survival of geriatric patients was compared with other patients. Results: HER2 receptor positivity, advanced-stage tumors (T3–T4), a high NPI, and Luminal B subtypes were significant predictors of worse outcomes. Conversely, Luminal A tumors, associated with favorable hormonal responsiveness, demonstrated the best progression-free survival (PFS). HER2-positive patients exhibited a poorer PFS compared to their HER2-negative counterparts, underscoring the need for careful management of aggressive subtypes in older adults. Additionally, patients undergoing mastectomy were less likely to receive adjuvant therapies, contributing to inferior outcomes compared to breast-conserving surgery (BCS). Conclusions: Mastectomy, HER2 positivity, high NPI, advanced stages, and Luminal B tumors are significant prognostic factors in geriatric breast cancer patients.